Identifikasi Potensi dalam Upaya Perencanaan Masterplan Desa Wisata Sumbersawit, Magetan, Jawa Timur - Pratiwi Anjar Sari; Vita Fibri Taufiq Hidayat; Ade Fitria Yupa (Syntax Corporation Indonesia, 2024)
Sumbersawit Village is located on the slopes of Mount Lawu and has a natural panorama that can be a promising tourism potential. The village government has ideas for the development of village tourism, but until now it has not been able to develop well due to the lack of resources and the role of actors in the development of village tourism. The method used in this research is descriptive exploratory which aims to describe a phenomenon and describe chronologically the data and facts in the field. The data obtained is then processed using the triangulation method. This technique analyzes data from various data sources, including observation data, interviews, and secondary data. The use of this analysis technique aims to combine all data in order to produce a precise and comprehensive conclusion. The results of the research show that Sumbersawit Village has the potential of an agritourism village which is divided into 3 areas namely Growong, Sawit and Miri. The results of potential mapping can be used as a reference in the development of a tourist village master plan.